Quantitative investigations of xylose and arabinose substituents in hydroxypropylated and hydroxyvinylethylated arabinoxylans. (1st November 2017) - Lorenz, Dominic; Knöpfle, Anna; Akil, Youssef; Saake, Bodo
Highlights: Arabinoxylans were chemically modified with cyclic carbonates. Detailed characterization of hydroxyalkylated and hydroxyvinylethylated xylans. Illustration of the pentose substitution patterns showed elongation of side chains. Elongation of side chains is preferred for hydroxyvinylethylated pentoses. Compared to xylose, the reaction with arabinose is preferred. Abstract: The chemical structures obtained by the modification of arabinoxylans with the cyclic carbonates propylene carbonate (PC) and 4‐vinyl-1, 3-dioxolan-2-one (VEC) with varying degrees of substitution were investigated. Therefore, a new analytical method was developed that is based on a microwave-assisted hydrolysis of the polysaccharides with trifluoroacetic acid and the reductive amination with 2-aminobenzoic acid. The peak assignment was achieved by HPLC–MS and the carbohydrate derivatives were quantified by HPLC-fluorescence. The obtained maximum molar substitution of PC-derivatized xylan (XHP ) was 1.8; the molar substitution of VEC-derivatized xylan (XHVE ) was 2.3. Investigations of xylose and arabinose based mono- and disubstituted derivatives revealed a preferred reaction of the cyclic carbonates with arabinose. Conversion rates were up to 2.4 times higher for monosubstitution and up to 3.0 times for disubstitution compared to xylose. Furthermore, the reaction with VEC was preferred due to higher reactivity of the newly introduced side chains.